2000
DOI: 10.1128/jcm.38.6.2181-2185.2000
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Low-Level Bacteremia in Children from Birth to Fifteen Years of Age

Abstract: A single blood culture inoculated with a small volume of blood is still frequently being used for the diagnosis of bacteremia in children because of the continued belief by many that bacteria are usually found in high concentrations in the blood of pediatric patients with sepsis. To determine the importance of both blood volume cultured and the number of culture devices required for the reliable detection of pathogens in our pediatric population, blood from children from birth to 15 years of age and with suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(35 citation statements)
references
References 42 publications
0
34
0
1
Order By: Relevance
“…Adequate blood culture volume was defined for 3 age groups, based on the same criteria used in the previous study 4 : ≥0.5 mL and ≤4.0 mL for patients ≤1 month of age 2,10 ; ≥1.0 mL and ≤4.0 mL for patients >1 month to 36 months of age; and ≥4.0 mL and ≤10.0 mL for patients >36 months of age. 2,5,6,11-14 A blood culture was considered to be submitted in an appropriate bottle if a PF bottle was used in a child <3 years old and a FA bottle used if ≥4 years old. FN bottles were considered appropriate in any age group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate blood culture volume was defined for 3 age groups, based on the same criteria used in the previous study 4 : ≥0.5 mL and ≤4.0 mL for patients ≤1 month of age 2,10 ; ≥1.0 mL and ≤4.0 mL for patients >1 month to 36 months of age; and ≥4.0 mL and ≤10.0 mL for patients >36 months of age. 2,5,6,11-14 A blood culture was considered to be submitted in an appropriate bottle if a PF bottle was used in a child <3 years old and a FA bottle used if ≥4 years old. FN bottles were considered appropriate in any age group.…”
Section: Methodsmentioning
confidence: 99%
“…4 In children, the volume of blood submitted for culture is frequently small. 5 Reasons for this include difficulty in obtaining blood from infants and children, avoidance of taking large quantities of blood relative to total blood volume, and the belief that less blood is needed as bacterial loads are greater in sepsis in this age group. 5…”
Section: Introductionmentioning
confidence: 99%
“…It was thought that bacterial colony forming units were far greater in the blood of younger patients than that of adults, hence the lower volume was conceptualised as being sufficient to yield a positive result in children and neonates 8. However, subsequent studies demonstrated that lower levels of bacteraemia may be more common in paediatric patients than was previously thought 9 10. Hence smaller blood volumes from younger patients may potentially increase false-negative cultures.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…During the past two decades, staphylococci have emerged as the main cause of septicaemia in paediatric intensive care units (PICUs), and are associated with extended stay and therapy, and invasive procedures [1,2]. The collection of blood specimens from PICU patients poses problems in relation to the low circulating blood volume and the difficulty in documenting low-level bacteraemia [3,4]. Blood culture methods have been developed for exclusive use in children, with different formulations and volumes of broth, e.g., FAN bottles (Organon-Teknika, Durham, NC, USA).…”
mentioning
confidence: 99%
“…Some reports [8,9] have suggested that the blood inoculation volume is of little importance for paediatric and neonatal studies, while others have recommended inoculation with a blood volume of 10-20% [10,11] or 4-4.5% [4] of total circulating blood volume, calculated to be c. 70 mL ⁄ kg [12]. The present study found that use of a very small inoculation volume (0.5 mL) did not result in a decrease in the IR compared with a procedure using 1.5 mL.…”
mentioning
confidence: 99%